Favorite Lecturer Characters of Elementary Education Teacher Prospective Students - Zulaikhah, Zulaikhah; Hidayati, Ani; Chikmah, Lailatul; Wahyuningsih, Sri; Jarong, Koree; Malik, Muh Syauqi (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2024)
This research aims to discover the character aspects of lecturers most preferred by Elementary education students and the impacts and implications on the character of prospective teacher students. The method used in this research is qualitative field research with phenomena studies. Primary data were obtained from students through a questionnaire using a form instrument and unstructured interviews with an open pattern. The results showed that of the 13 aspects of lecturer character that were the most favored aspects of prospective Elementary School teacher students mapped from lecturer personality and educational competencies, namely lecturers who were able to place themselves, had high self-confidence, were tolerant, and understood students' character. The impact on students is increased motivation and self-confidence, more positive relationships, increased academic achievement, and development of student soft skills. The implications of the character of a favorite lecturer for the character of prospective teacher students are the formation of an Inclusive Learning environment, increased student psychological well-being, and strengthening of a positive academic culture.